2016
DOI: 10.3109/13880209.2015.1135966
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor pracinostat in doublet therapy: a unique strategy to improve therapeutic efficacy and to tackle herculean cancer chemoresistance

Abstract: Context Histone deacetylase inhibitors (HDACi) have shown promising results in neurodegeneration and cancer. Hydroxamate HDACi, including vorinostat, have shown encouraging results in haematological malignancies, but the poor pharmacokinetic of these inhibitors leads to insufficient tumour concentration limiting their application against solid malignancies. Objective This article deals with novel HDAC inhibitor pracinostat (SB939) and delineates its therapeutic role in solid and haematological malignancies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…While HATs favor the transcriptional activation via chromatin decondensation, HDACs promote chromatin condensation and subsequent gene silencing (Yang and Seto, 2007 ). The opposing activities of HATs and HDACs regulate acetylation homeostasis that plays a crucial role in governing various gene expression programs (Ropero and Esteller, 2007 ; Ganai, 2016a ). HDACs are conjugated enzymes modulating both histone and non-histone substrates and act as corepressors in transcriptional events (Yang and Seto, 2008 ; Mottamal et al, 2015 ; Ganai, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While HATs favor the transcriptional activation via chromatin decondensation, HDACs promote chromatin condensation and subsequent gene silencing (Yang and Seto, 2007 ). The opposing activities of HATs and HDACs regulate acetylation homeostasis that plays a crucial role in governing various gene expression programs (Ropero and Esteller, 2007 ; Ganai, 2016a ). HDACs are conjugated enzymes modulating both histone and non-histone substrates and act as corepressors in transcriptional events (Yang and Seto, 2008 ; Mottamal et al, 2015 ; Ganai, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Romidepsin followed SAHA in gaining approval and is currently used against CTCL and peripheral T-cell lymphoma (PTCL) (Ververis et al, 2013 ). Belinostat, the third HDAC inhibitor has been approved for relapsed/refractory PTCL (Ververis et al, 2013 ; Ganai, 2016a ). The fourth approved inhibitor panobinostat is currently active against multiple myeloma (Ganai, 2016c ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, SB939 was shown to have anticancer properties, and was shown to have maximum efficacy in doublet therapy. In addition, pracinostat shows these same results against more therapeutically challenging cancers 7 . SB939 was also cited as a viable treatment drug for acute myeloid leukemia based on the studies discussed above 8 .…”
Section: Introductionmentioning
confidence: 82%
“…Among them, Pracinostat 1 is a promising compound, which has been granted breakthrough therapy designation by FDA for the treatment of patients with newly diagnosed acute myelocytic leukemia (AML) who are ≥75 years of age or unfit for intensive chemotherapy(Abaza et al., ; Garcia‐Manero et al., ). Currently, Pracinostat is undergoing phase III clinical trials (Abaza et al., ; Ganai, ; Garcia‐Manero et al., ; Kang et al., ; Novotny‐Diermayr et al., ).…”
Section: Introductionmentioning
confidence: 99%